2020
DOI: 10.15252/embj.2019103661
|View full text |Cite
|
Sign up to set email alerts
|

Distinct retrograde microtubule motor sets drive early and late endosome transport

Abstract: Although subcellular positioning of endosomes significantly impacts on their functions, the molecular mechanisms governing the different steady-state distribution of early endosomes (EEs) and late endosomes (LEs)/lysosomes (LYs) in peripheral and perinuclear eukaryotic cell areas, respectively, are still unsolved. We unveil that such differences arise because, while LE retrograde transport depends on the dynein microtubule (MT) motor only, the one of EEs requires the cooperative antagonism of dynein and kinesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 96 publications
2
11
0
Order By: Relevance
“…As we have described here, STIM and Orai proteins are increasing recognized as regulating cellular functions beyond the classic Ca 2+ meditated transcription pathways. In addition to metabolic and mitochondrial regulation and cell survival, a protein complex including STIM1 is responsible for trafficking of early and late endosomes ( Villari et al, 2020 ), consistent with its identification as a microtubule plus-end tracking protein. This could have wide ranging implications given the numerous fundamental functions of the endolysosomal system including metabolic signaling, plasma membrane remodeling autophagy and cell migration ( Bonifacino and Neefjes, 2017 ).…”
Section: Discussionmentioning
confidence: 76%
“…As we have described here, STIM and Orai proteins are increasing recognized as regulating cellular functions beyond the classic Ca 2+ meditated transcription pathways. In addition to metabolic and mitochondrial regulation and cell survival, a protein complex including STIM1 is responsible for trafficking of early and late endosomes ( Villari et al, 2020 ), consistent with its identification as a microtubule plus-end tracking protein. This could have wide ranging implications given the numerous fundamental functions of the endolysosomal system including metabolic signaling, plasma membrane remodeling autophagy and cell migration ( Bonifacino and Neefjes, 2017 ).…”
Section: Discussionmentioning
confidence: 76%
“…Another open question is which kinesins are required for the transport of Hrs and STAM1 under basal conditions, as KIF13A knockdown does not seem to impair this process. Several kinesins in addition to KIF13A and KIF13B, including KIF5A/B/C, KIFC1, and KIF16B, have been implicated in endosomal trafficking ( Bonifacino & Neefjes, 2017 ; Li et al, 2020 ; Villari et al, 2020 ) and may also have roles in the axonal transport of ESCRT-0 proteins. Clearly, additional work is needed to identify other cargoes of KIF13A, as well as the specific motor proteins responsible for anterograde and retrograde transport of Hrs+ vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The directional movement of vesicles is determined by various microtubule motor proteins that move toward the periphery (e.g., kinesin superfamily proteins KIF5 and KIF3) or perinuclear region (e.g., KIFC1, 2, and 3) depending on the plus or minus orientation of the microtubules to which they attach ( Hirokawa et al, 2009 ; Camlin et al, 2017a ; Muralidharan and Baas, 2019 ). A recent study assessing the microtubule motor control of early endosomes in human endothelial cells demonstrated that simultaneous silencing of KIFC1 and stromal interaction molecule 1 (STIM1) resulted in more peripherally distributed EEA1 positive early endosomes ( Villari et al, 2020 ). Aligning with this, Kifc1 gene and KIFC1 protein expression decreases in the aged oocyte, with functional siRNA-mediated knockdown and pharmacological inhibition of Kifc1 /KIFC1 in young oocytes recapitulating hallmarks of poor oocyte quality such as increased aneuploidy rates ( Mihalas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%